Maternal healthcare service utilisation and associated factors among mothers in a rural Wolaita, southern Ethiopia: a community-based cross-sectional study - Wondimagegn Paulos Kumma; Abera Kuche (BMJ Open)
Objective To assess the level of maternal healthcare service utilisation and related factors to its frequency of care among mothers who gave birth in the previous 2 years before the survey in rural Wolaita, southern Ethiopia.Design Cross-sectional survey.Setting This study was undertaken in Kindo Didaye, rural Wolaita, southern Ethiopia, from February to March 2016.Participants Out of 552 who gave birth, 544 (98.5%) mothers aged between 15 and 49 years, selected using two-stage random sampling, participated in the study.Outcome measures Maternal healthcare service utilisation frequency and proportion and associated factors.Result The proportion of maternal healthcare service utilisation was 59.38% (95% CI: 55.11% to 63.53%), with 50.74% (95% CI: 46.45% to 55.01%), 16.18% (95% CI: 13.18% to 19.54%) and 31.80% (95% CI: 27.90% to 35.90%) prevalence of antenatal care (ANC), delivery care and postnatal care (PNC), respectively. The frequency of maternal healthcare service utilisation was positively related to having a favourable attitude towards maternal healthcare service utilisation, knowledge of mothers about maternal healthcare, walking distance to healthcare facilities in 30 and 30–60 min from residence and joint decision by mothers and their husbands on the place of delivery.Conclusion The proportion of maternal healthcare service utilisation in the study area was low, exacerbated by lower ANC, delivery care and PNC. The frequency of maternal healthcare service utilisation increased with a favourable attitude towards maternal healthcare service utilisation, knowledge of mothers about maternal healthcare, short travel distance to healthcare facilities and joint decisions by mothers and their husbands on the place of delivery. Based on the findings of this study, we suggest promoting strategies by the local health department and other concerned bodies to maintain and improve the attitude and knowledge of mothers towards maternal healthcare service utilisation. We also recommend increasing the accessibility to healthcare facilities and promoting joint decision-making processes by the mothers and their husbands on the place of delivery in the study area and similar settings in the country.